2022
DOI: 10.1108/apjml-01-2022-0084
|View full text |Cite
|
Sign up to set email alerts
|

What affects users to click social media ads and purchase intention? The roles of advertising value, emotional appeal and credibility

Abstract: PurposeThis study is based on a web-based advertising value model, adding emotional appeal, advertising credibility, advertising clicks, product evaluation and incentive to examine the impact on consumers' product evaluation and purchase intention.Design/methodology/approachIn total, 313 valid online questionnaires were collected from those who had browsed the social media advertisement.FindingsThe results show that advertising credibility and emotional appeal have a higher impact on advertising attitude than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…In terms of advertising value, previous research has used entertainment, informativeness, and irritation as constructs of advertising value [21,26]. However, traditional advertising value constructs are not entirely appropriate for the social media advertising context due to the differences between social and traditional media [10]. Therefore, in addition to the traditional constructs of advertising effectiveness, new constructs are needed to explain SNS users' positive response behavior (i.e., empathy expression).…”
Section: Sns Advertising Effectivenessmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of advertising value, previous research has used entertainment, informativeness, and irritation as constructs of advertising value [21,26]. However, traditional advertising value constructs are not entirely appropriate for the social media advertising context due to the differences between social and traditional media [10]. Therefore, in addition to the traditional constructs of advertising effectiveness, new constructs are needed to explain SNS users' positive response behavior (i.e., empathy expression).…”
Section: Sns Advertising Effectivenessmentioning
confidence: 99%
“…Thus, the primary purpose of advertising information is to provide consumers with information about new products or services. Previous research has shown that information is essential for developing consumers' attitudes toward e-commerce websites [13] and social media advertisements [10,20]. Lee and Koo [45] believe that informational advertisements on social media will attract users' attention and affect users' attitudes to form positive responses.…”
Section: Informativenessmentioning
confidence: 99%
See 3 more Smart Citations